FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PEMILIHAN KARIR MAHASISWA AKUNTANSI SEBAGAI AUDITOR PEMERINTAH (Studi Empiris Mahasiswa Jurusan Akuntansi UGM, UI, Unri, Unand, UIN Suska dan UIR) - Syaftinov Eka Putra; Hardi '; Afiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The rapid economic growth would make a lot of the work force to compete for jobs. No exception for graduate students majoring in accounting economy both at public and private universities. Competition in the business world certainly encourage them to become students qualified and ready to enter the world of work. For that they must be equipped with the ability to both since the college and outside the college to enable them to have competence in the world of work.The objective of this study to examine the influence of Motivation Market, Economic Motivation, Work Environment, Individual Personality, Professional Training and Professional Recognition for Career Selection of Student Accounting toward Government Auditor. The questionnaire used as an instrument of this study were distributed a total of 154 copies to the University Accreditation A (UGM and UI), 215 copies to the University Accreditation B (UNRI and UNAND), and 265 copies for the University Accreditation C (UIN SUSKA and UIR) of the students the period 2013 who has taken a major concentration and has proposed proposal. Data collected were analyzed using multiple regression analysis version 19.0. The result of this study proved that Influence of Motivation Market, Economic Motivation, Work Environment, Individual Personality, Professional Training and Professional Recognition has signifiant influenced toward Career Selection of Student Accounting to have been Government Auditors as multiple correlation coefficient (R) of 0,825 and a strong relationship.Keywords: Interest, Career, Accounting, Auditor and Government